Biết \(\displaystyle\int\limits_0^1\dfrac{3x-1}{x^2+6x+9}\mathrm{\,d}x=3\ln\dfrac{a}{b}-\dfrac{5}{6}\), trong đó \(a,\,b\) là hai số nguyên dương và \(\dfrac{a}{b}\) là phân số tối giản. Tính kết quả \(ab\).
\(-5\) | |
\(7\) | |
\(12\) | |
\(6\) |
Chọn phương án C.
Đặt $A=\displaystyle\int\limits_0^1\dfrac{3x-1}{x^2+6x+9}\mathrm{\,d}x$ ta có $$A+\dfrac{5}{6}=3\ln\dfrac{a}{b}\Leftrightarrow\mathrm{e}^{\tfrac{6A+5}{18}}=\dfrac{a}{b}.$$
Vậy $a=4$ và $b=3$. Do đó $ab=12$.
Chọn phương án C.
\(\begin{eqnarray*}
&&\displaystyle\int\limits_0^1\dfrac{3x-1}{x^2+6x+9}\mathrm{\,d}x\\
&=&\displaystyle\int\limits_0^1\dfrac{3x+9-10}{(x+3)^2}\mathrm{\,d}x\\
&=&\displaystyle\int\limits_0^1\dfrac{3}{x+3}\mathrm{\,d}x - \displaystyle\int\limits_0^1\dfrac{10}{(x+3)^2}\mathrm{\,d}x\\
&=&\left(3\ln|x+3|+\dfrac{10}{x+3}\right)\bigg|_0^1\\
&=&3\ln \dfrac{4}{3}-\dfrac{5}{6}.\end{eqnarray*}\)
Theo đó \(a=4,\,b=3\Rightarrow ab=12\).